2020
DOI: 10.1111/clr.13620
|View full text |Cite
|
Sign up to set email alerts
|

Abstracts presented at the European Association for Osseointegration (EAO) Congresses: Publication fate and discrepancies with full‐length articles

Abstract: Objectives: To investigate the full publication proportion (FPP) of abstracts presented at the 2010 and 2011 EAO Congresses, analyse the discrepancies between abstracts and their full publications, and explore potential predictors of FPP and discrepancies.Methods: Abstracts presented at the 2010 and 2011 EAO Congresses were retrieved.Associated full publications were identified by searching PubMed, Embase and Google Scholar. Discrepancies between abstracts and full publications were identified, classified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…Another factor that may have hindered identification of full-text articles is discrepancies in the authorship and title reported on the initial abstract and subsequent article. In the assessment of full publication rate of presented oral implantology abstracts, discrepancies in both authorship (73.5%) and title (71.8%) were prevalent (Wu et al, 2020). An assessment of the study quality of presented abstracts and methodology was not undertaken in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that may have hindered identification of full-text articles is discrepancies in the authorship and title reported on the initial abstract and subsequent article. In the assessment of full publication rate of presented oral implantology abstracts, discrepancies in both authorship (73.5%) and title (71.8%) were prevalent (Wu et al, 2020). An assessment of the study quality of presented abstracts and methodology was not undertaken in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Common discrepancies include quantitative outcomes, sample size and statistical significance. Despite the reported benefits of abstracts, their sole use to inform clinical practice is not advocated (Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, some scholars have found that the published articles are not completely consistent to the abstracts presented at the conference ( Chalmers, Frank & Reitman, 1990 ; Van den Bogert et al., 2017 ). Wu et al. (2020) found at least one discrepancy between the conference abstracts of European Association for Osseointegration and the published article abstracts in terms of title, statistical method, main results, and sample size.…”
Section: Introductionmentioning
confidence: 83%
“…It is possible that the search strategy did not accurately identify all publications, although the selection, inclusion, and analysis methods were based on similar investigations 1 , 5 , 7 , 9 , 14 , 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%